Geographic and historical texts from the lost book "Al-Masalik wa al-Mamalik" by Muḥammad b. Yūsuf al-Warrāq (d. 363 AH/974 AD), collection of two works "Al-Maghrib" of Al-Bakri and "Al-Bayan" of Ibn Adhari al-Marrakushi - ziani, Sadek (The Algerian Historical Journal, 2026)
This study attempts to compile a collection of geographic and historical texts from the lost book" Al-Masalik wa al-Mamalik" by Muhammad ibn Yusuf al-Warraq of Qayrawan, drawing on excerpts from this work found in Al-Bakri's geography (died in 478 AH/1094 AD) and Ibn Adhari's informational compilation (died after 712 AH/1312 AD). We have compiled and classified informational and geographic texts covering the 4th Islamic century and earlier periods, including ethnic and religious related to the Ismaili, Khawarij, and Nukkaris groups, as well as tribal groups like the Lawata, Zanata, and Banu Hamdun. These texts also contain geographic information, personalities and figures associated with the Fatimid Caliphate, Umayyad Caliphate and Zirid Dynasty. Overall, we have determined the importance of the texts contained in al-Warrāq's book, and regret the loss of many texts from it.